Automated 3D analysis of multislice computed tomography to define the line of perpendicularity of the aortic annulus and of the implanted valve: Benefit on planning transcatheter aortic valve replacement. Issue 1 (10th June 2013) - Samin, Mariam; Juthier, Francis; Van Belle, Camille; Agostoni, Pierfrancesco; Kluin, Jolanda; Stella, Pieter R.; Ramjankhan, Faiez; Budde, Ricardo P.J.; Sieswerda, Gertjan; Algeri, Emanuela; Elkalioubie, Ahmed; Belkacemi, Anouar; et al.
<x xml:space="preserve">Abstract</x> Aims We aimed to determine whether preprocedural analysis of multislice computed tomography (MDCT) scan could accurately predict the "line of perpendicularity" (LP) of the aortic annulus and corresponding C‐arm angulations required for prosthesis delivery. Methods and Results A 3D analysis of preprocedural MDCT dedicated to define the LP of the aortic annulus was performed in 60 consecutive patients referred for transcatheter aortic valve replacement (TAVR). In 24 patients, the analysis was performed retrospectively to evaluate reproducibility. In 11 patients of this cohort, additional fluoroscopy and MDCT were performed postprocedure to compare the LP of the aortic annulus and the LP of the implanted bioprosthesis. In 36 patients, the analysis was performed prospectively and the results were available at the time of the procedure. In those 36 patients, the postprocedure fluoroscopy‐defined LP of the implanted bioprosthesis was used to validate the LP of the aortic annulus as predicted by MDCT. Intraobserver and interobserver reproducibility of the 3D analysis of MDCT to define the LP of the aortic annulus (κ = 1 and 0.94, respectively) and of the bioprosthesis (κ= 1 and 1, respectively) were excellent. Comparison between the LP of the aortic annulus and the LP of the bioprosthesis showed that the two LPs were virtually identical, demonstrating both self‐centering of the device during implantation and the possibility to use the LP of the implanted bioprosthesis as a surrogate of the LP of the aortic annulus. In the prospective cohort, the ability of MDCT analysis to predict the LP of the aortic annulus was very good (accuracy = 94% and κ = 0.89). Conclusion Automated 3D analysis of preimplantation MDCT accurately predicts the LP of the aortic annulus and the corresponding C‐arm position required for TAVR.© 2013 Wiley Periodicals, Inc.